Effect of Oral Administration of Royal Jelly towards Fertility Performance of Rabbit through Artificial Insemination - Tan, Y J Y; Wakil, A M; Sukri, S A Mohamad; J Stephen,; Khalif, R I A Raja (Animal Reproduction Update, 2025)
The rabbit livestock industry is rising rapidly as an alternative protein source in  Malaysia. As the global population increases, alternative food sources such as  rabbit-based products are important for meeting human demand for livestock  products. Optimization of rabbit production relies on reproductive technology.  Assisted reproduction technologies (ART) like artificial insemination (AI) are being  introduced to the farmer to maximize the production of the rabbit industry. However,  local livestock farmers still need to improve their knowledge and technique. Thus,  this study aims to investigate the fertility rate of does using artificial insemination  compared to natural mating (NM) and to determine the effect of different  concentrations of oral administration of royal jelly (RJ) on semen fertility in rabbits.  A total of 12 bucks and 20 does of American White rabbits (Oryctolagus cuniculus)  were used, with ages between 7 to 12 months and average body weights of 2.5 to 3  kg. The bucks were assigned to 4 experimental groups for oral administration: (a)  control A, 0 mg/kg of royal jelly; (b) control B, 0 mg/kg of royal jelly; (c) treatment 1,  100 mg/kg of royal jelly; and (d) treatment 2, 50 mg/kg of royal jelly. Control A rabbit  was mated naturally, while the other groups were mated using AI. Sperm quality  was evaluated through physical criteria: volume, colour, pH, odour, and viscosity.  Pregnancy diagnosis (manual abdominal palpation, real-time ultrasound) was  performed to evaluate the conception rate of the doe. The result that the conception  rate of natural mating (83.33%) was higher compared to artificial insemination  (16.13%). Moreover, oral administration of royal jelly showed a negative effect on  the conception rate of does, where 0 mg/kg of royal jelly showed 36.36%, 100 mg/kg  showed 0%, and 50 mg/kg showed 10% of conception rate.
Keywords: Rabbit; Royal Jelly; Fertility Performance; Artificial Insemination; Pregnancy diagnosis; Ultrasound